Implementasi Teknik RET dan REBT dalam Teori Psikologis di SMAN 5 Tasikmalaya - Arif Hidayat; Feida Noor Laila Isti; Refa Muthia Bilqisthi; Tiara Anindya Jufiantira; Sabrina Salsa Aulia; Indy Nurshalshabila; Ines Febri Fitriyah (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Psychology is a scientific discipline that aims to understand human behavior. The differences in human behavior in response to the presence of stimulus have proven that every human being is unique and not the same, and their needs are different. No human being is the same psychologically even though their physical condition looks the same to the naked eye. This affects human abilities as well when faced with the source of the problem at hand. Every human being must constantly develop their competence, so as not to experience a mental crisis that can eventually lead to pathological disorders. Understanding human uniqueness especially in cognitive, affective, and psychomotor abilities will help in the smoothness of the counseling process. At SMAN 5 Tasikmalaya, the counseling process is not based on psychological theory alone, but depends on the student. How to approach students who have problems at this high school with one of the ways in each class there is 1 hour of counseling lessons a week, so that students do not have fear, but students become more courageous to consult the BK teacher.